National Culture and Entrepreneurship : A Review of Behavioral Research - Hayton, James C.; George, Gerard; Zahra, Shaker A. (Entrepreneurship Theory and Practice, 2002)
Conceptual arguments for the association between cultural characteristics and entrepreneurship have existed for decades but only in the last 10 years has this relationship been the focus of empirical scrutiny. In this article, we review and synthesize the findings of 21 empirical studies that examine the association between national cultural characteristics and aggregate measures of entrepreneurship, individual characteristics of entrepreneurs, and aspects of corporate entrepreneurship. The study concedes that a predominant number of empirical studies have used Hofstede's conceptualization of national culture and that other domains have been underdeveloped. A preliminary model that integrates past findings is extended. The review highlights fruitful avenues for future research.